Carotid Intima Media Thickness Reference Intervals for a Healthy Argentinean Population Aged 11-81 Years - Diaz, Alberto Alejandro (2018)
Reference intervals (RIs) of carotid intima media thickness (CIMT) from large healthy population are still lacking in Latin America. The aim of this study was to determine CIMT RIs in a cohort of 1012 healthy subjects from Argentina. We evaluated if RIs for males and females and for left and right carotids were necessary. Second, mean and standard deviation (SD) age-related equations were obtained for left, right, and average (left + right)/2) CIMT using parametric regression methods based on fractional polynomials, in order to obtain age-specific percentiles curves. Age-specific percentile curves were obtained. Males showed higher A-CIMT ( mm versus  mm, ) in comparison with females. For males, the equations were as follows: A-CIMT mean = 0.42 + ; A-CIMT SD = 5.9 × 10−2 + . For females, they were as follows: A-CIMT mean = 0.40 + ; A-CIMT SD = 4.67 × 10−2 + . Our study provides the largest database concerning RIs of CIMT in healthy people in Argentina. Specific RIs and percentiles of CIMT for children, adolescents, and adults are now available according to age and gender, for right and left common carotid arteries.